Deep integration and production networks: An empirical analysis - Gianluca Orefice; Nadia Rocha (World Trade Organization (WTO), 2011)
In this paper, the two way relationship between deep integration and production networks trade is investigated. Deep integration is captured by a set of indices constructed in terms of policy areas covered in preferential trade agreements. An augmented gravity equation is estimated to investigate the impact of deep integration on production networks. The results show that on average, signing deeper agreements increases production networks trade between member countries by almost 35 percentage points. In addition, the impact of deep integration is higher for trade in automobile parts and information and technology products compared with textiles products. To analyse whether higher levels of network trade increase the likelihood of signing deeper agreements the literature on the determinants of preferential trade agreements is followed. The estimation results show that, after taking into account other PTAs determinants, a ten per cent increase in the share of production network trade over total trade increases the depth of an agreement by approximately 6 percentage points. In addition, the probability of signing deeper agreements is higher for country pairs involved in North-South production sharing and for countries belonging to the Asia region.
Keywords: F13; F15; F14; 330; regionalism; deep integration; production networks; Handelsregionalismus; Außenhandelspräferenz